2014
DOI: 10.1007/s00421-014-2895-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of β-alanine and NaHCO3 co-ingestion on buffering capacity and exercise performance with high-intensity exercise in healthy males

Abstract: Introductionβ-alanine (BAl) and NaHCO3 (SB) ingestion may provide performance benefits by enhancing concentrations of their respective physiochemical buffer counterparts, muscle carnosine and blood bicarbonate, counteracting acidosis during intense exercise. This study examined the effect of BAl and SB co-supplementation as an ergogenic strategy during high-intensity exercise.MethodsEight healthy males ingested either BAl (4.8 g day−1 for 4 weeks, increased to 6.4 g day−1 for 2 weeks) or placebo (Pl) (CaCO3) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 36 publications
6
47
1
13
Order By: Relevance
“…Indeed, such is the wealth of published studies on sodium bicarbonate, that recently, researchers have started to focus on its co-ingestion with other active ingredients such as caffeine 24,25 and -alanine 26,27,28 in order to assess the potential additive effects in order to provide further performance enhancements via the activation of different ergogenic mechanisms simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, such is the wealth of published studies on sodium bicarbonate, that recently, researchers have started to focus on its co-ingestion with other active ingredients such as caffeine 24,25 and -alanine 26,27,28 in order to assess the potential additive effects in order to provide further performance enhancements via the activation of different ergogenic mechanisms simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Danaher et al [4] also reported no influence on performance following NaHCO3 supplementation in men using a similar dosage and testing protocol to those used in the present study. Despite a significant increase in pre-exercise blood bicarbonate following supplementation in their study, the authors stated that metabolic alkalosis was not achieved due to a lack of change in blood pH following NaHCO3 supplementation [4]. They did not elucidate why there was no change, as several investigations using the same protocol have previously shown changes in pH after the ingestion of similar doses of NaHCO3 [224,252,253].…”
Section: Rsa -Nahco3 Supplementationsupporting
confidence: 67%
“…Using an almost identical testing and dosage protocol to that used in the present study, Danaher et al [4] reported no change in RSA performance after six weeks of β-alanine supplementation (4.8 g·day −1 for 4 weeks, 6.4 g·day −1 for final 2 weeks). However, participants did not train during the supplementation period.…”
Section: Rsa -Training and β-Alanine Supplementationmentioning
confidence: 54%
See 2 more Smart Citations